2018
DOI: 10.3390/math6110242
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Network-Based Model Predictive Control for Continuous Pharmaceutical Manufacturing

Abstract: The pharmaceutical industry has witnessed exponential growth in transforming operations towards continuous manufacturing to effectively achieve increased profitability, reduced waste, and extended product range. Model Predictive Control (MPC) can be applied for enabling this vision, in providing superior regulation of critical quality attributes. For MPC, obtaining a workable model is of fundamental importance, especially in the presence of complex reaction kinetics and process dynamics. Whilst physics-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…Datadriven ML approaches, on the other hand, which primarily rely on data rather than the physics and thermodynamics of these processes, offer a more generic and computationally faster approach for sustainable design, process monitoring, quality control, and effective system integration in a manufacturing environment. [37,57] Lv et al [40] sourced data from the ERP system and devised an artificial neural network (ANN) and neighborhood component feature selection-coupled ANN (NCFS-ANN) using a set of 40 input features to predict the scrap rate and material feeding (target labels) during the production of printed circuit boards and observed that the performances of the NCFS-ANN were better than the standalone ANN model. Li et al [41] presented an online monitoring approach to predict the surface roughness of 3D-printed parts during the fused filament fabrication process using the process data sourced from in situ sensors.…”
Section: For Shop Floor Monitoring and Controlmentioning
confidence: 99%
“…Datadriven ML approaches, on the other hand, which primarily rely on data rather than the physics and thermodynamics of these processes, offer a more generic and computationally faster approach for sustainable design, process monitoring, quality control, and effective system integration in a manufacturing environment. [37,57] Lv et al [40] sourced data from the ERP system and devised an artificial neural network (ANN) and neighborhood component feature selection-coupled ANN (NCFS-ANN) using a set of 40 input features to predict the scrap rate and material feeding (target labels) during the production of printed circuit boards and observed that the performances of the NCFS-ANN were better than the standalone ANN model. Li et al [41] presented an online monitoring approach to predict the surface roughness of 3D-printed parts during the fused filament fabrication process using the process data sourced from in situ sensors.…”
Section: For Shop Floor Monitoring and Controlmentioning
confidence: 99%
“…Lee [42] proposes a cost/benefit model to asses and predict the impact of quality investments on returned profit in a multi-level production assembly. A non-linear mathematical model was proposed by Iqbal and Sarkar [43] to give an optimum amount of preservatives to increase the lifetime of products, while Wong et al [44] studied waste reduction in pharmaceutical manufacturing. The study suggests that the preservation-based improved life length of products is associated with the price of the products, as the coordination of certain aspects like costs and quality of products in a supply chain infrastructure is a fundamental parameter in keeping product cost in-control and making a supply chain profitable.…”
Section: Preservation Tecniquesmentioning
confidence: 99%
“…System identification is an important branch in the field of modern control and is an important method to establish systematic mathematical models from the combination of observation data and prior knowledge [1][2][3][4][5][6][7][8], and has been applied in many fields for decades, such as controller design [9][10][11][12][13][14][15] and system analysis [16][17][18][19][20]. Parameter identification is an important part of system identification and is to estimate the parameters by using the measurable data [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%